Detection of Epstein-Barr virus genomes in Hodgkin's disease: relation to age. Issue 10 (October 1991) - Jarrett, R F; Gallagher, A; Jones, D B; Alexander, F E; Krajewski, A S; Kelsey, A; Adams, J; Angus, B; Gledhill, S; Wright, D H
Abstract : An investigation as to whether any particular subgroup of patients with Hodgkin's disease was particularly likely to be Epstein-Barr virus (EBV) genome positive was made on samples from 95 patients. These were grouped according to age and Hodgkin's disease subtype, and analysed using Southern blot analysis. Most samples from children or adults aged 50 years or over contained detectable EBV genomes; samples from young adults were only rarely positive. The differences in EBV positivity by age were highly significant, but there was no significant association between EBV and histological subtype after allowing for the effect of age. The results support the hypothesis that Hodgkin's disease in different age groups may have different aetiologies, and suggest that EBV does have a pathogenetic role in Hodgkin's disease in children and older age groups.